The human right to adequate food and sustainable development goals: collective interferences with children in vulnerable urban peripheries - Frutuoso, Maria Fernanda Petroli; Viana, Cássio Vinícius Afonso; Mendes, Rosilda; Almeida, Paulo Santos de; Wallerstein, Nina; Akerman, Marco (Saúde e Sociedade, 2022)
This study aimed to analyze the relation between the Human Right to Adequate Food (HRAF) and Sustainable Development Goals (SDG) resulting from a dialogic experience with children and adolescents in the periphery of São Vicente, São Paulo. Using the methodological framework of participatory research, community assemblies observation, and the partnership between the university and social movements point to a caring place for children/adolescents that enable collective diagnostic readings on food. Dialogical processes enable us to problematize HRAF dimensions based on the chain of food production, trading and consumption, and the instability to which those children/adolescents are subjected in a complex network of determinants that produce hunger and malnutrition in the territories in which they live. Results show that these dimensions dialogue with all the SDGs, as they demand cultural, economic, social, and environmental sustainability of food. The partnership and integration between university and society strengthens and enhances the spaces of social control and training of actors to advocate for the HRAF. It can also change inequalities in the territories and acknowledge children as subjects of rights with deep ethical commitment in the construction of inclusive listening and qualified practices.